RESONANCES IN ASTEROID SYSTEMS - Troianskyi, V. (Одеські астрономічні публікації, 2016)
Today the following types of resonances in the rotation of celestial bodies in the solar system are known, namely orbital, spin-orbit and spin-spin resonances. This paper presents our computations of these types of resonances for the known binary and multiple asteroid systems.